1994
DOI: 10.1364/ao.33.005118
|View full text |Cite
|
Sign up to set email alerts
|

Automated multifilter rotating shadow-band radiometer: an instrument for optical depth and radiation measurements

Abstract: The multifilter rotating shadow-band radiometer is a ground-based instrument that uses independent interference-filter-photodiode detectors and the automated rotating shadow-band technique to make spectrally resolved measurements at seven wavelength passbands (chosen at the time of manufacture between 350 nm and 1.7 µm) of direct-normal, total-horizontal, and diffuse-horizontal irradiances. This instrument achieves an accuracy in direct-normal spectral irradiance comparable with that of tracking radiometers, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
277
0
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 432 publications
(287 citation statements)
references
References 8 publications
0
277
0
6
Order By: Relevance
“…A detailed description of the operation principles of the MFR can be found in Harrison et al (1994a), and a considerable number of publications have suggested various algorithms for the retrieval of aerosol optical depths from measurements of the direct solar irradiance (e.g. Bruegge at al., 1992;Michalsky et al, 2001;Alexandrov et al, 2002a).…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of the operation principles of the MFR can be found in Harrison et al (1994a), and a considerable number of publications have suggested various algorithms for the retrieval of aerosol optical depths from measurements of the direct solar irradiance (e.g. Bruegge at al., 1992;Michalsky et al, 2001;Alexandrov et al, 2002a).…”
Section: Methodsmentioning
confidence: 99%
“…Particles in the troposphere scatter solar radiation, trap greenhouse thermal radiation, alter the amount of light reflected by the Earth, and increase the stability and brightness of the clouds. In addition, atmospheric aerosols contribute to acid rain and visibility impairment (19).…”
Section: Box 1 Urban Airmentioning
confidence: 99%
“…www.ijacsa.thesai.org It is also applied to measurement data of Multi-Filter Rotating Shadow Band Radiometer (MFRSR) [14] and is trying to use it for atmospheric correction [15]. Furthermore, accuracy comparison with regular LPM has also been done, proving that the precision according to (7) is higher [9].…”
Section: A Theoretical Backgroundmentioning
confidence: 99%